Eksistensi dan Standarisasi Pemeriksaan Perkara Dispensasi Kawin Berbasis Kepastian Hukum - Hidayatullah, Muhammad Syarif; Wahyudi, Firman; Saipullah, Saipullah (Syakhsiyah Jurnal Hukum Keluarga Islam, 2023)
This paper aims to analyze the existence of marriage dispensation with the handling of cases and the standardization of case examinations based on legal certainty. This study is based on normative legal research with a statutory approach and a conceptual approach. The presence of a marriage dispensation is the cause of marriages that have not reached the minimum age of marriage according to applicable law. The determination of the age limit of marriage is influenced by the 'urf that prevails in society by considering various advances that do not conflict with Islamic law. Religious Courts as parties that have authority in issuing marriage dispensations, must consider various aspects before approving applications for marriage dispensations such as sharia, sociological, psychological, juridical, and health aspects. Juridically with the provisions contained in article 5 of the Marriage Law, the phrase "very urgent reasons" opens up a space for diverse interpretations (multi-interpretation) for judges in dealing with marriage dispensation because the context of this phrase is in a general, not particular, meaning. There needs to be standardization in the case of this marriage dispensation application so that there is a unity of mind that realizes legal certainty.